2019
DOI: 10.1093/jpepsy/jsz078
|View full text |Cite
|
Sign up to set email alerts
|

Topical Review: State of the Field of Child Self-Report of Acute Pain

Abstract: Objective Children experience acute pain with routine and emergent healthcare, and untreated pain can lead to a range of repercussions. Assessment is vital to diagnosing and treating acute pain. Given the internal nature of pain, self-report is predominant. This topical review reflects on the state of the field of pediatric acute pain self-report, and proposes a framework for acute pain assessment via self-report. Method We e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
11
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 51 publications
1
11
0
Order By: Relevance
“…Data within a single study and across studies suggest that associations between FPS-R and FLACC range from no significant relationship to strong correlations (da Silva et al, 2011;Emmott et al, 2017). Consistent with the perspective that self-report and observer-report scales might be reflecting different-and valuable-aspects of the same event (Cohen et al, 2008), our findings underscore that we assessed different outcomes in line with the longstanding recommendation that pediatric procedural pain assessment be conducted in a multimethod manner (American Academy of Pediatrics Committee on Psychosocial Aspects of Child and Family Health; Task Force on Pain in Infants, Children and Adolescents;Cohen et al, 2020;McGrath & Gillespie, 2001).…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…Data within a single study and across studies suggest that associations between FPS-R and FLACC range from no significant relationship to strong correlations (da Silva et al, 2011;Emmott et al, 2017). Consistent with the perspective that self-report and observer-report scales might be reflecting different-and valuable-aspects of the same event (Cohen et al, 2008), our findings underscore that we assessed different outcomes in line with the longstanding recommendation that pediatric procedural pain assessment be conducted in a multimethod manner (American Academy of Pediatrics Committee on Psychosocial Aspects of Child and Family Health; Task Force on Pain in Infants, Children and Adolescents;Cohen et al, 2020;McGrath & Gillespie, 2001).…”
Section: Discussionsupporting
confidence: 83%
“…The program was grounded in the rich literature documenting successful cognitive-behavioral strategies for pediatric procedural distress management (e.g., Cohen et al, 2017). For example, data generally suggest that parent presence is optimal if they are trained in strategies to minimize their child's distress, such as avoiding certain behavior (e.g., excessive reassurance, criticism) and engaging in coping promoting behavior (e.g., distraction; Cohen et al, 2020). Further, studies have shown that preparation is effective and should include information about procedural steps as well as sensory experiences (Jaaniste et al, 2007).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…49 The self-report scales used extensively in clinical and research settings also have real limitations. 42 Pain is recognized as multidimensional, yet the majority of scales use global estimates of pain intensity 50 that obscure the richness of the experience 51 and sacrifice the potential for interventions varyingly targeting cognitive, emotional, or social features of the experience. 52 As well, pain ratings can be biased by modest changes in instructions or subtle differences in scale items.…”
Section: A Ss E Ss Ment and Me A Surementmentioning
confidence: 99%
“…While pain intensity is not typically informative where pain is already anticipated to be strong (i.e., post-surgery), it is relevant to caregivers who manage acute pain events regularly. Gathering pain intensity ratings from the child, using validated but simple assessments such as the S-FPS, may allow caregivers to assess pain quickly and determine whether further treatment is required (Cohen et al, 2019). Future studies could consider whether additional measures can provide a reliable means of drawing young children into conversations about their own pain.…”
Section: Discussionmentioning
confidence: 99%